PELATIHAN PENINGKATAN KEMAMPUAN GADIK DAN GADIKAN DALAM RANGKA PEMBELAJARAN OGANISASI POLRI PADA PROGRAM PENDIDIKAN PEMBENTUKAN BINTARA POLRI DI SPN POLDA JAWA BARAT - Sari, Deti Yuanita; Ansori, Ansori; Widiastuti, Novi (IKIP Siliwangi, 2024)
This study aims to determine the planning of training to increase the ability of girls and women in the context of learning about the Police organization in the National Police Formation Education program at the SPN Polda West Java. To find out the implementation of improving the ability of girls and girls in the context of learning about the Police organization in the National Police Formation Education program at the SPN Polda West Java. To describe the results of improving the ability of girls and girls in the context of learning the Polri organization in the National Police NCO Formation Education program at the SPN Polda West Java, this research uses a case study research base and a qualitative descriptive type of research. Determination of informants is done by purposive sampling, which is chosen intentionally with the consideration that the selected informants are considered capable of providing the required information. The results of this study prove that the organization directs to whom members of the organization interact and communicate so that it is not considered wrong (ethically and disciplined) both in attitude and behavior, especially in person to person relationships. On the other hand, it also has a relationship and is interrelated, namely influencing the management of the organization that appears in the form of decisions, policies and directives, both written and verbal. This organizational training encourages orderly learning management because apart from keeping open the pattern of two-way communication, discussion and dialogue, it also includes criticism, input and suggestions. However, organizational training requires that communication be formally guided by certain ethics, procedures and procedures